CHANGES IN SOME DIAGNOSTIC PARAMETERS OF THE FUNCTIONAL STATE OF THE LIVER IN DOGS WHILE USING EPS “IMMUNOBACTERIN-D” - Rybachuk, Zh. V.; Galatyuk, O. Ye.; Demchuk, Yu. S.; Antonyuk, A. A.; Solodka, L. O. (Scientific Progress & Innovations, 2020)
The results of using the “Immunobacterin-D” enzyme-probiotic supplement to German shepherd breed dogs are presented in the article. It is found that the inclusion of 1 gram supplement to the morning feed dose per animal once a day for 14 days causes a positive effect on the dogs’ organism. Namely reliable (P≤0.001) decrease in alanine aminotransferase activity in dog blood serum of the experimental group as compared with indicators of the intact group from 24.86±1.45 to 18.93±1.8 U / l was observed after 14 days. During the next observation (up to 35 days) the tendency to the decrease was maintained. A decrease of 5.2 times in the activity of gamma glutamyltranspeptidase 14 days after applying the enzyme-probiotic supplement was reported. Besides, only 1.9 times decrease in the activity of GGTP was found in the serum of animals of the control group. No significant changes in the activity of alkaline phosphatase in the dog serum of the experi- mental and control groups were reported. We believe that such indicators of GGTP activity are indicative of intrahepatic bile stasis in the liver of animals. The decrease in the activity of AST, SGPT and GGTP in the serum of dogs who ate “Immunobacterin-D” with the feed was due to a decrease in the toxic loading of the liver because of active reproduction of symbiotic microflora and protease activity and inhibition of vital ac- tivity of pathogenic micro-flora in the intestine, as it is well known that phenol, cresol (formed by phenylala- nine and tyrosine microflora) and scatol and indole (synthesized from tryptophan) are neutralized in the liv- er. It was also reported that the blood serum of experimental animals had significantly (P≤0.001) more cal- cium ions before including the “Immunobacterin-D” in the diet, but during the next month of observation, their number decreased and was almost identical to that in the control group. In this case, phosphorus con- tent did not differ significantly from the control group and were within the physiological range. So, the dy- namic, significant decrease (P≤0.001) of SGPT activity indicates the improvement of hepatocyte functioning, which is possibly stipulated by a decrease in antigenic and toxic liver loading as a result of the symbiotic effect of Bac. subtilis and Bac. licheniformis probiotic microorganisms.